Reseña de: Puig, Isidro; Company, Ximo; Garrido, Carmen; Herrero, Miguel Àngel, Francisco de Goya. Carlos IV. Lleida, CAEM-Universitat de Lleida, 2016. isbn: 978-84-8409-857-7 Páginas: 168. - Vigara Zafra, José Antonio (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2017)
Puig, Isidro; Company, Ximo; Garrido, Carmen; Herrero, Miguel Àngel, Francisco de Goya. Carlos IV. Lleida, CAEM-Universitat de Lleida, 2016. isbn: 978-84-8409-857-7 Páginas: 168.